(3aUhU GdMces - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi QCjJ QShd Gddg Udi Gddg Ydjg hSde ai eHTQI QCjJgG ai GdYTQ GdCNQ ef GdeMQe hHjOg Udi Gddg Ydjg hSde cJGH abGd di gPG aUhU GdMce s
(3BNQgG (B:s
(3hGdTF dGjbGd ajg jSY faSg hdGdGjSYgG aGage hGddg jbhd GdMb hgh jgOi GdSHjd ced GdcJGH HMeO Gddg GdhgGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1261s
Keywords: (3GdJUha hGdBOGH GdTQYjIs